ANALYSIS OF THE EFFECT OF INTEREST RATE ON LOAN AND FINANCIAL LOAN IN THE PRESENCE OF FINTECH IN INDONESIA - Mawey, Keisy; Tasik, Hizkia (Universitas Sam Ratulangi, 2019)
Abstract: Fintech revolution has led to a great transformation in the banking sector. While fintech is continuing to grow, credit tends to slow down. The presence of Fintech is affecting the market. People that used to consider interest rate as the standard to borrow from conventional banks, now prefer to borrow from Fintech that offer an ease of access. This research aims to analyze the effect of interest rate on loan and financial loan in the presence of fintech in Indonesia. This study uses quantitative method. Secondary data from Central Bank data are used to collect the data. The sample of this study are State banks, Regional Development banks, Private banks and Foreign and Joint banks in Indonesia. This research examined the model through data panel regression model. Finding of this research shows that before the presence of Fintech, Working Capital Interest Rate, Investment Interest Rate and Consumption Interest Rate are significantly affecting Loan in general and Financial Loan but after the presence of Fintech, Consumption Interest rate become the only variable left that significantly affects Loan in general and Financial Loan. The conventional banks need to reconsider the regulations of loan to make the customers easier to access the loans.Â Keywords: fintech, interest Rate, loan, financial Loan